Inhibition of RelA phosphorylation sensitizes apoptosis in constitutive NF-kappaB-expressing and chemoresistant cells - Manna S.K.; Manna P.; Sarkar A. (My University, 2025)
The compound 5-(4-methoxyarylimino)-2-N-(3,4-dichlorophenyl)- 3-oxo-1,2,4-thiadiazolidine (P3-25) is known to possess anti-bacterial, anti-fungal, anti-tubercular, and local anesthetic activities. We studied the anti-tumorigenic activity of P3-25 and the role of nuclear transcription factor kappaB (NF-κB) in this process. In constitutive NF-κB-expressing cells, treatment with P3-25 inhibited the expression of NF-κB-dependent reporter gene, adhesion molecules, and cyclooxygenase. It downregulated phosphorylation of p65 by inhibiting upstream kinases, such as protein kinase A and casein kinase II, but did not alter NF-κB DNA-binding activity. Alone, P3-25 induced apoptosis in NF-κB-expressing and doxorubicin-resistant breast cancer cells, and in the presence of other chemotherapeutic agents, it potentiated apoptosis. Overall, our results suggest that P3-25 exerts antitumorigenic activity by inhibiting phosphorylation of p65, the transcriptionally active subunit of NF-κB by inhibiting its upstream kinases, and potentiates apoptosis mediated by chemotherapeutic agents. These results suggest novel approaches for designing of anticancer drugs for combination chemotherapy.